Dampak Variabel Produk, Promosi, dan Harga Terhadap Keputusan Konsumen Dalam Membeli Krupuk Ayam Bawang di Desa Krembangan Taman Sidoarjo - Intan Febria Nita; Aridha Prasetya; Harsono Teguh Santoso; Bambang Karnain; Sugiharto Sugiharto; Achmad Daengs GS (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
Competition is so tight now that companies must be able to play reliable marketing strategies and be able to attract consumer interest so they can win the market. Products that have good quality with good differentiation will be products that are most likely to have loyal consumers. By understanding how consumer behavior will contribute to companies formulating marketing strategies which will later be implemented in introducing and promoting their products to the market. This means that when a product is to be produced, it is known long beforehand what the consumer's needs and desires are. After the company has formulated a strategy that will be implemented in an effort to gain consumers' attention, building good communication with consumers is a step that must be taken by the company to consumers and must be done on an ongoing basis. With this effort, it will be known how consumers respond to the product.